2017
DOI: 10.1039/c7tb01681f
|View full text |Cite
|
Sign up to set email alerts
|

Two-level delivery systems for oral administration of peptides and proteins based on spore capsules of Lycopodium clavatum

Abstract: Two-level delivery systems for oral administration of therapeutic proteins and peptides were developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…It was found that after 96 h incubation in SBF the magnitudes of changes were extremely diminished, which confirms the functional role of human blood plasma in SDMCs degradation. This correlates well with the literature that reports the physical degradation of SECs in human/rat blood and plasma but not in SBF or serum 9,17 .…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…It was found that after 96 h incubation in SBF the magnitudes of changes were extremely diminished, which confirms the functional role of human blood plasma in SDMCs degradation. This correlates well with the literature that reports the physical degradation of SECs in human/rat blood and plasma but not in SBF or serum 9,17 .…”
Section: Resultssupporting
confidence: 92%
“…However, broken SDMCs were seen to be altered into irregular pieces with aspect ratios between 0.5 and 0.6. Hence, it can be inferred that the observed population shift in terms of aspect ratio following blood plasma incubation is a result of partial degradation rather than complete breakage, which would agree with previously reported scanning electron microscopy images of partially degraded SECs that were treated in rat blood for 30 min 17 .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations